An Improved BM Pattern Matching Algorithm in Intrusion Detection System - Yin, Chao (Applied Mechanics and Materials, 2011)
An improved BM-algorithm in intrusion detection system was presented which can increase displacements using the next character of the substring has been matched in the main string and pattern string. Experimental results obtained by capturing network packets with the number of matches, the number of pattern moves, the number of character comparisons as the main indicators. Experimental results show that the number of matches after and before improved is equal, and the number of pattern moves decreased by about13.3% after improved, and the number of character comparisons decreased by about 15.1% after improved. This indicates that the improved algorithm improved the efficiency of pattern matching.